Propostas de procedimentos para projetar filtros harmônicos a partir de um programa de penetração harmônica, incluindo cálculos de desempenho e de suportabilidade - Nascimento, Rogério Pinto do (2007)
This work introduces some proposals for the design of harmonic filters from a harmonic penetration computer program. Such procedures are developed by means of optimized techniques, taking in account, among other aspects, the filtering performance, the filter detuning as well as international guides referring to the supportability of the filter components, as far as voltage, current and power are concerned. The work shows the need for designing filters through a harmonic penetration program. Therefore, the filter parameters can be calculated not only from harmonic currents driven from a single harmonic source (as usually it is made), but also from other existing (and unwanted) harmonic sources eventually present in the system, which could eventually be attracted by the harmonic filter. The work also introduces some studies of cases, in which single tuned filters are compared to damped filter. This study is made in a typical industrial plant, where an arc furnace (that produces characteristic and non-characteristic harmonic) is present. The study shows, among other aspects that, depending on some important requirements made in the design of the filters, a damped filter arrangement can be more advantageous than a single tuned one.